UTILIZATION OF VARING PROPORTIONS OF UREA-TREATED SUGAR CANE SCRAPPINGS AND GROUNDNUT HAULMS IN THE DIETS OF GROWING YANKASA RAMS - Bashir, S. S.; Abubakar, M.; Sani, I. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study evaluated the utilization of varying Proportion of urea-Treated sugarcane scrappings (SS) and Groundnut haulms in the diets of Growing Yankasa rams. Sixteen (16) Yankasa Rams were randomly assigned to four treatment groups, each with four rams in a completely randomized design. Four experimental diets were formulated with SS, and GH, T1 (7.5), T2 (15%), T3 (22.5%), and T (30%). GH T1 (30%), T2 (22.5%), T3 (15%), and T4 (7.50%). Labeled as T1, T2, T3, and T4 respectively. The results revealed significant differences (p<0.05) in the final weight gain. Rams on T1 had the highest final weight gain (23.30 kg), while those on T4 had the lowest (20.32 kg). The total weight gain and daily weight gain were similar across treatments, with T2 showing a slightly higher daily gain (0.10 kg/day). Feed intake was highest in T1 (50.77 kg) and decreased with increasing levels of groundnut haulm. Feed conversion ratios were lowest in T2 (6.74) and highest in T1 (7.55). Haematological parameters varied significantly among treatments. Rams on T3 had the highest packed cell volume (46.8%), while T4 showed the highest hemoglobin concentration (18.4 g/dL) and mean corpuscular hemoglobin concentration (41.5 g/dL). Serum biochemistry revealed that total protein was highest in T4 (32.20 g/L), while glucose levels were within the reference range for all treatments. Urea and cholesterol levels were also within the normal ranges, with T3 showing the highest urea (9.7 mmol/L) and T1 the highest cholesterol (2.0 mmol/L). Rumen pH at 0 hours before feeding (BF) ranged from 6.60 in T4 to 6.90 in T3. Five hours after feeding (AF), the pH varied, with T3 showing the lowest pH (5.97) and T4 the highest (6.94). Rumen ammonia nitrogen (RAN) was highest in T1 at both 0 hours BF (51.49 mg/dL) and 5 hours AF (68.41 mg/dL). Total volatile fatty acids (VFA) were highest in T2 at 0 hours BF (84.89 mmol/100) and in T3 at 5 hours AF (127.61 mmol/100). In conclusion, the inclusion of sugar cane scrapping up to 30% in the diet did show adverse effect on Yankasa Rams. It is recommended to include sugar cane scrapping and groundnut haulm at levels of 15% to 22.5% in the diets of Yankasa Rams to achieve optimal growth and health benefits.